A Bacillus subtilis ΔpdxT mutant suppresses vitamin B6 limitation by acquiring mutations enhancing pdxS gene dosage and ammonium assimilation. Issue 2 (4th March 2021) - Richts, Björn; Lentes, Sabine; Poehlein, Anja; Daniel, Rolf; Commichau, Fabian M.
Summary: Pyridoxal‐5′‐phosphate (PLP), the biologically active form of vitamin B6, serves as a cofactor for many enzymes. The Gram‐positive model bacterium Bacillus subtilis synthesizes PLP via the PdxST enzyme complex, consisting of the PdxT glutaminase and the PdxS PLP synthase subunits, respectively. PdxT converts glutamine to glutamate and ammonia of which the latter is channelled to PdxS. At high extracellular ammonium concentrations, the PdxS PLP synthase subunit does not depend on PdxT. Here, we assessed the potential of a B. subtilis Δ pdxT mutant to adapt to PLP limitation at the genome level. The majority of Δ pdxT suppressors had amplified a genomic region containing the pdxS gene. We also identified mutants having acquired as yet undescribed mutations in ammonium assimilation genes, indicating that the overproduction of PdxS and the NrgA ammonium transporter partially relieve vitamin B6 limitation in a Δ pdxT mutant when extracellular ammonium is scarce. Furthermore, we found that PdxS positively affects complex colony formation in B. subtilis . The catalytic mechanism of the PdxS PLP synthase subunit could be the reason for the limited evolution of the enzyme and why we could not identify a PdxS variant producing PLP independently of PdxT at low ammonium concentrations.